2021
DOI: 10.3389/fimmu.2021.761382
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exercise Intensity on Th1/Th2 Immune Modulations During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has led to several pioneering scientific discoveries resulting in no effective solutions with the exception of vaccination. Moderate exercise is a significant non-pharmacological strategy, to reduce the infection-related burden of COVID-19, especially in patients who are obese, elderly, and with additional comorbidities. The imbalance of T helper type 1 (Th1) or T helper type 2 (Th2) cells has been well documented among populations who have suffered as a result of the COVID-19 pandemic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 140 publications
(147 reference statements)
3
20
0
Order By: Relevance
“…These responses are efficacious in raising antiviral immunity while activating antibody responses. Th1 responses are regulated by T cells which mainly express IFN-gamma and IL-2, and they have a key role in attracting immune cells to the site of infection and in mediating the T-cell cytotoxicity of infected cells; Th2 responses are regulated by T cells expressing mainly IL-4 and IL-10, and they are involved in efficacious antibody production and airway inflammation observed in some respiratory diseases [ 75 ]. On the other hand, Th17 responses are regulated by T cells expressing IL-17, IL-6 and IFN-gamma.…”
Section: Advantages and Caveats Of Efficacy And Safety Of Mrna Sars-c...mentioning
confidence: 99%
“…These responses are efficacious in raising antiviral immunity while activating antibody responses. Th1 responses are regulated by T cells which mainly express IFN-gamma and IL-2, and they have a key role in attracting immune cells to the site of infection and in mediating the T-cell cytotoxicity of infected cells; Th2 responses are regulated by T cells expressing mainly IL-4 and IL-10, and they are involved in efficacious antibody production and airway inflammation observed in some respiratory diseases [ 75 ]. On the other hand, Th17 responses are regulated by T cells expressing IL-17, IL-6 and IFN-gamma.…”
Section: Advantages and Caveats Of Efficacy And Safety Of Mrna Sars-c...mentioning
confidence: 99%
“…The disproportionality of T helper type 1 (Th1) or Th2 cells has been well elucidated in patients suffered from COVID-19 pandemic and non-infected people who are at maximum risk of infection ( 26 ). In an observational study,COVID-19 patients have been reported to have lower proportion of Th1 and Th17 cells and a higher proportion of activated Th2 cells compared with control population ( 27 ).…”
Section: Immune Responses In Covid-19mentioning
confidence: 99%
“…The immune response plays vital roles in the development of respiratory diseases and cancer. 11,12 PM can increase the risk of these diseases by the dysfunction of the immune cells and their regulatory pathway. 24 As far as we know, this work is the first to explore the potential effects and exposure−response relationships of PM components on the T-cell response in population.…”
Section: Discussionmentioning
confidence: 99%
“…Immune systems take an important part in the development of respiratory diseases and cancers. , T lymphocytes, pluripotent stem cells derived primarily from bone marrow, differentiate and mature in thymus . T lymphocytes (CD4 + , CD8 + T cells, etc.)…”
Section: Introductionmentioning
confidence: 99%